DETERMINAN BIAYA MODAL EKUITAS (Studi Empiris pada Perusahaan Manufaktur yang terdaftar di BEI) - Septian Ardi Prabowo, 10.05.52.0187; Hardiningsih, Pancawati (Students Journal of Accounting and Banking, 2014)
This study was to analyze the effect of voluntary disclosure and earnings management to information asymmetry and cost of equity with the perspective of agency theory and signaling theory. As per agency theory and the theory of agency conflict resolution signal to signal to the user information needs of enterprise information.This study research used purposive sampling to select a sample with a sample of 66 companies listed in Indonesia Stock Exchange (BEI) in the period 2010-2012. The analysis used is multiple regression analysis. Results of studies using regression proves that voluntary disclosure does not significantly negatively to the asymmetry of information,earnings management is positively significant effect on information asymmetry, information asymmetry does not significant positively effect to cost of equity, voluntary disclosure does not significantly negatively affect to cost of equity, earnings management is positively significant effect on the cost of equity. Keywords: Voluntary Disclosure, Earnings Management, Information Asymmetry, Cost of Equity Â